2013
DOI: 10.1002/biof.1096
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and health

Abstract: Over the last decades, a considerable body of evidence supported the hypothesis that diet and dietary factors play a relevant role in the occurrence of diseases. To date, all the major scientific associations as well as the World Health Organization and the nonscientific organizations place an ever-increasing emphasis on the role of diet in preventing noncommunicable diseases. Many studies have evaluated the associations between food groups, foods, or nutrients and chronic diseases, and a consensus about the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(117 citation statements)
references
References 39 publications
2
107
0
8
Order By: Relevance
“…Los factores dietéticos pueden modificar el perfil de riesgo poblacional para enfermedades crónicas y la hipótesis que asocia una dieta adecuada con salud cardiovascular ha ganado cada vez mayor aceptación en el mundo científico 1 . La dieta mediterránea (DMed) es considerada uno de los patrones dietarios con mayor evidencia científica acumulada en cuanto a sus beneficios en salud humana, siendo cada vez mayor el interés del mundo científico en el estudio de su rol preventivo y como tratamiento en diversas patologías asociadas a inflamación crónica, como síndrome metabólico (SM), diabetes, enfermedad cardiovascular (ECV), enfermedades neurodegenerativas y cáncer, entre otras 2 . De hecho, en las últimas décadas, el número de publicaciones en el tema ha crecido en forma exponencial, alcanzando cerca de 500 artículos en Pubmed en el año 2014 (Figura 1).…”
unclassified
“…Los factores dietéticos pueden modificar el perfil de riesgo poblacional para enfermedades crónicas y la hipótesis que asocia una dieta adecuada con salud cardiovascular ha ganado cada vez mayor aceptación en el mundo científico 1 . La dieta mediterránea (DMed) es considerada uno de los patrones dietarios con mayor evidencia científica acumulada en cuanto a sus beneficios en salud humana, siendo cada vez mayor el interés del mundo científico en el estudio de su rol preventivo y como tratamiento en diversas patologías asociadas a inflamación crónica, como síndrome metabólico (SM), diabetes, enfermedad cardiovascular (ECV), enfermedades neurodegenerativas y cáncer, entre otras 2 . De hecho, en las últimas décadas, el número de publicaciones en el tema ha crecido en forma exponencial, alcanzando cerca de 500 artículos en Pubmed en el año 2014 (Figura 1).…”
unclassified
“…Toplumlara farklı türlerde tıbbi beslenme tedavisi ilkeleri önerilmiş olmakla birlikte, dikkati en çok Akdeniz diyeti çekmektedir. 13 1960'lı yıllardan beri Akdeniz diyeti önemli sağlık etkileri nedeni ile ilgi odağı olmuştur. 1 …”
Section: Akdeni̇z Di̇yeti̇ni̇n Potansi̇yel Sağlik Etki̇leri̇unclassified
“…3 Akdeniz diyeti, hafif şişmanlık ve şişmanlığın önlenmesi ve düzeltilmesi konularında ilgi görmektedir. 2,13 Şişmanlık ve Akdeniz diyeti ile ilgili potansiyel ters ilişki mekanizmaları aşağıda açıklanmıştır: Diyet Posası Ayrıca, çiğneme tükürük salgısı ve gastrik asit üretimini artırır ve böylece gastrik distansiyon artar. Ek olarak, posadan zengin besinler fazla miktarda su içermektedir.…”
Section: Akdeni̇z Di̇yeti̇ Ve şİşmanlikunclassified
“…Adherence to Mediterranean diet has been investigated as a protective factor against some non-communicable chronic diseases including cardiovascular disease, diabetes and many type of cancer (18). Although some studies showed that Mediterranean diet decrease the risk of breast cancer, the association of Mediterranean dietary pattern and the incidence of breast cancer is controversial.…”
Section: Mediterranean Dietary Pattern and Risk Of Breast Cancermentioning
confidence: 99%